Characterization of Laser Structuring on AISI 304 Stainless Steel - Edan, Sarah Sabah; Taha, Rana M. (Al-Nahrain Journal for Engineering Sciences, 2025)
Super-hydrophobic is the tendency of a surface to spit out water droplets. Only a surface with high apparent contact angle (>1500), low contact angle hysteresis (<100), low sliding angle (<50), and strong Cassie model state stability is considered a super-hydrophobic surface. In an attempt to create highly hydrophobic synthetic surfaces suitable for a range of uses, attempts have been made to mimic the super-hydrophobicity found in natural materials (such as lotus leaves). Due to its wide range of applications including waterproof, anti-fog, anti-ice and anti-corrosion surface, the laser processing process achieved the use of process parameters which had a significant impact on the roughness factor. High roughness factor F. At constant values of p = 3 mW and ω = 10 μm, at scanning speeds of 6000 mm/s.